الزراعة الذكية ومتطلبات تطبيقها لتحقيق استدامة الأمن الغذائي في الدول العربية: Smart agriculture and the requirements for its application to achieve sustainable food security in the Arab countries - بن شاعة نادية; حضري دليلة (Journal of North African Economies, 2025)
Smart agriculture is an important solution to achieve food security and ensure its sustainability in light of the pressures experienced by the global food system. Many countries have adopted smart farming methods in order to achieve a comfortable food situation while preserving their resources. That smart agriculture is an agriculture that preserves the environment and resources, which makes it a means to reduce the negative effects of climate change , which makes it a suitable solution for Arab countries that suffer from a large food deficit, and although there are some Arab experiences in this field, they are not sufficient given the need for these smart methods in the field of agriculture in order to reduce the problem of food security and preserve resources, Arab countries must take scientific and deliberate steps to adopt smart agriculture.